RestRho: A JSON-Based Domain-Specific Language for Designing and Developing RESTful APIs to Validate RhoArchitecture - Chavarriaga, Enrique; Rojas, Luis; Rodríguez, Francy D.; Sorbello, Kat; Jurado, Francisco (Future internet, 2025)
Domain-Specific Languages with JSON grammar (JSON-DSLs) are specialized programming languages tailored to specific problem domains, offering higher abstraction levels and simplifying software implementation through the JSON standard. RhoArchitecture is an approach for designing and executing JSON-DSLs, incorporating a modular programming model, a JSON-based evaluation engine, and an integrated web development environment. This paper presents RestRho, a RESTful NodeJS server developed using two JSON-DSLs designed with RhoArchitecture: SQLRho and DBRestRho. These languages enable declarative specification of database operations and HTTP requests, respectively, supporting modularity, reuse, and template-based transformations. We validate the RestRho implementation through a dual approach. First, we apply software metrics to assess code quality, maintainability, and complexity. Second, we conduct an empirical study involving 39 final-year computer engineering students, who completed 18 structured tasks and provided feedback via questionnaires. The results demonstrate the tool’s usability, development efficiency, and potential for adoption in web application development.